IMPLEMENTASI MEDIA PEMBELAJARAN ZOOM MEETING TERHADAP MINAT BELAJAR MAHASISWA SEKOLAH TINGGI TEOLOGI DUTA PANISAL JEMBER - Gusuli Ndruru; Tri Wurianingsih Laksono (Sekolah Tinggi Teologi Duta Panisal, 2022)
Online learning is a solution for the limited learning activities during the current pandemic. Internet-based distance learning media is the right choice to replace face-to-face learning, including video conferencing such as Zoom Meetings. Online lectures need to be packaged in an innovative way to attract students interest in learning. Interest is a strong source of motivation in learning and triggers one's participation/activity. This is the background of the author to conduct research with the title